Social capital, participation in agricultural production cooperatives and economic empowerment among farmers in Isfahan, Iran - Nasrabadi, Mohsen Koohi (2012)
The present thesis is an investigation of participation, social capital and farmer’s economic empowerment (FEE) in agricultural production cooperatives (APCs) in the rural area in Isfahan Province in Iran. It aims to develop a framework for empowerment to analyze farmer’s economic empowerment. This current thesis begins with an exploration of empowerment and it argues about the concept and philosophy and theories of empowerment. It then builds a conceptual framework of farmer’s economic empowerment. Using this framework, three elements of farmer’s economic empowerment (FEE) are outlined as follow: enterprise development of farmers, financial assets and marketing strategies. It continues with an explanation of dimensions of articipation, subjective and objective participation. Then, it builds a conceptual framework for social capital.Three proxies of social capital and two proxies of participation were measured in this study,among which social trust appeared as the contributing factor or key function of economic empowerment. It was the most significant social capital variable which contributed to the level of overall economic empowerment of members of APCs. Objective participation, subjective participation and social solidarity were also found to be the key factors in enhancing the farmer's economic empowerment. It is concluded that social trust and social solidarity as two dimensions of social capital and participation are positively affecting on economic empowerment of farmers in agricultural production cooperatives in Isfahan Province in Iran.